INTEGRATED MANAGEMENT OF SOYBEANRUST: Life Science-Agriculture - M. HEGDE, GURUDATT; K.MESTA, RAGHAVENDRA (International Journal of Life Science and Pharma Research, 2012)
The rust disease of soybean caused by the fungal pathogen which named Phakopsora pachyrhizi(Sydow) could cause soybean rust, was the most destructive pathogen and caused soybean yield declined by 20-80%. In the present investigation, a botanical fungicide, neem seed kernal extract along with hexaconazole, propiconazole and triadimefon had reduced the disease severity of rust disease. Three sprays of hexaconazole alone have considerably reduced disease severity to higher level (9.54%) and resulted in significantly higher seed yield (24.79q/ha), 100 seed weight (14.37), lesser Area Under Disease Progress Curve (AUDPC) (339.03) and highest B: C (7.07:1) ratio. The nimbicidine in the spraying schedule with other fungicides was found to be effective in reducing percent disease index and area under disease progress curve. Though the yield in treatment (H-H-H) was highest (24.79 q/ha) compared to H-N-H (19.82q/ha) and P-N-P (19.41q/ha) the quality traits like protein and oil contents were on par with each other. The B: C ratio of 3.85:1 in H-N-H indicated that the inclusion of nimbicidine in the spray schedule is more useful not only in reducing the cost of protection but also gave higher benefits in addition to giving insurance against resistance development by the fungus against hexaconazole.